Keterlibatan Muslim dalam Politik Lokal di Negara-Negara Mayoritas Non-Muslim - Fathul Wahab, M. Royyan Nafis (Hunafa: Jurnal Studia Islamika, 2023)
The primary objective of this study is to get a comprehensive understanding of the socio-political status of Muslim individuals inside non-Muslim majority countries. Specifically, it wants to examine the various hurdles Muslims encounter in these contexts and the tactics they employ to navigate and surmount these obstacles. This research explores the surrounding community’s reactions and attitudes toward Muslims’ political engagements. The research method employed in this study is qualitative, utilizing a library research approach to gather data. The data is collected through an extensive review of pertinent literature. The study’s findings indicate that Muslims actively and strategically engage in local politics to achieve integration while preserving their religious identity. Despite encountering prejudice and discrimination, many individuals adhering to the Islamic faith have successfully surmounted these obstacles by establishing support networks and engaging in collaborative efforts with various groups. The responses of society towards Muslim engagement have exhibited a range of outcomes, with interfaith education and discussion emerging as useful strategies in fostering comprehension and acceptance. In conclusion, the active participation of Muslims in municipal politics holds the potential to engender constructive transformations and foster a culture characterized by inclusivity.